Can robots possess knowledge? Rethinking the DIK(W) pyramid through the lens of employees of an automotive factory - Hautala Johanna (SPRINGERNATURE, 2022)
Knowledge, information, and data are increasingly processed in human-robot collaboration. This study tackles two requirements for revising the concepts of knowledge, information, and data. First is developing robots' knowledge capabilities and transparency and ensuring effective division of tasks between humans and robots to increase the productivity of robotised factories. Employees' interpretations of robots' abilities to possess knowledge reveal their assumptions of robots' possibilities and limitations to create knowledge-based products with humans. Second, the classic DIK(W) pyramid of data, information, knowledge, and wisdom is a theoretical construct requiring additional empirical research. This empirical exploratory study develops the DIK(W) further and applies it as a tool to understand employees' perspectives of robots and knowledge. Do people believe robots possess knowledge? What kind of knowledge can (or cannot) robots possess? A survey (n = 269) was collected from the most robotised factory in Finland, Valmet Automotive. Half of the respondents think robots can possess knowledge, but only with humans. These respondents were more likely to trust robots compared to those who think robots cannot possess knowledge. As the key contribution, the DIK(W) pyramid is reconceived by (i) acknowledging robots and humans, (ii) turning the pyramid upside down, and (iii) recognising knowledge as a dividing concept.